Serum salusin-? levels in systemic lupus erythematosus and systemic sclerosis - Koca, Suleyman Serdar; Ozgen, Metin; Isik, Bahar; Dagli, Mustafa Necati; Ustundag, Bilal; Isik, Ahmet (Aves, 2014)
Objective: Systemic lupus erythematosus (SLE) and systemic sclerosis (SSc), chronic inflammatory diseases, demonstrate an increased incidence of cardiovascular manifestations and subclinical atherosclerotic disease. Salusin-alpha is a novel bioactive peptide that suppresses the formation of macrophage foam cells, and its serum level is significantly lower in patients with angiographically proven coronary artery disease. The aims of the study were to assess serum salusin-alpha level and its potential association with the predictors of atherosclerosis in SLE and SSc. Material and Methods: The study included 20 SLE and 22 SSc patients and 23 healthy controls (HC). All of the participants were female. Tumour necrosis factor-alpha (TNF-alpha), IL-6 and salusin-alpha levels, homeostasis model assessment for insulin resistance (HOMA-IR) index and common carotid intima-media thickness (IMT) were determined. Results: Salusin-alpha levels were lower and the IMTs were higher in the SLE and SSc groups than in the HC group. The salusin-alpha level was correlated with neither the disease activity scores nor cytokine levels and IMT in the SLE and SSc groups, although it was correlated with triglyceride level in the SLE group (r=-0.564, p=0.012), and with HOMA-IR index in the HC group (r=0.485, p=0.019). Conclusion: The present preliminary study may support the idea that SSc leads to subclinical atherosclerosis, as in SLE. Moreover, it can be concluded that the decreased salusin-a levels in SLE and SSc may contribute to subclinical atherosclerosis. However, further studies with larger sample size are needed to demonstrate this contribution in SLE and SSc.
Keywords: Systemic lupus erythematosus; systemic sclerosis; atherosclerosis; salusin-alpha